Contribution of P. falciparum parasites with Pfhrp 2 gene deletions to false negative PfHRP 2 based malaria RDT results in Ghana: A nationwide study of symptomatic malaria patients - Amoah, Linda Eva (PLoS One, 2020)
INTRODUCTION: False-negative malaria rapid diagnostic test (RDT) results amongst symptomatic malaria patients are detrimental as they could lead to ineffective malaria case management. This study determined the nationwide contribution of parasites with Pfhrp2 and Pfhrp 3 gene deletions to false negative malaria RDT results in Ghana. METHODS: This was a cross sectional study where whole blood (~2 ml) was collected from patients presenting with malaria symptoms at 100 health facilities in all the regions in Ghana from May to August 2018. An aliquot of the blood was used to prepare thin and thick blood smears, filter paper blood spots (DBS) and spot a PfHRP 2 RDT kit. The remaining blood was separated into plasma and blood cells and stored at -20°C. Plasmodium parasite density and species identity was estimated from the blood smears. Plasmodium falciparum specific 18S rRNA PCR, merozoite surface protein (msp 1) and glutamate rich protein (glurp) gene PCR were used to identify P. falciparum positive samples, which were subjected to Pfhrp 2/3 exon1-2 and exon2 genotyping. RESULTS: Of the 2,860 microscopically P. falciparum positive patients analyzed, 134 (4.69%) had false negative P. falciparum specific RDT results. Samples for PCR analysis was available for 127 of the false negative patients, and the analysis identified 116 (91.3%) as positive for P. falciparum. Only 58.1% (79/116) of the false negative RDT samples tested positive by msp 1 and glurp PCR. Genotyping of exon 1–2 and exon 2 of the Pfhrp 2 gene identified 12.9% (10/79) and 39.5% (31/79) of samples respectively to have deletions. Genotyping exon 1–2 and exon 2 of the Pfhrp 3 gene identified 15.2% (12/79) and 40.5% (32/79) of samples respectively to have deletions. Only 5% (4/79) of the false negative samples had deletions in both exon 1–2 and exon 2 of the Pfhrp 2 gene. Out of the 49 samples that tested positive for aldolase by luminex, 32.6% (16/49) and) had deletions in Pfhrp 2 exon 2 and 2% (1/49) had deletions in both exon 2 and exon 1–2 of the Pfhrp 2 gene. CONCLUSIONS: The low prevalence of false negative RDT test results provides assurance that PfHRP 2 based malaria RDT kits remain effective in diagnosing symptomatic malaria patients across all the Regions of Ghana. Although there was a low prevalence of parasites with deletions in exon 2 and exon 1–2 of the Pfhrp 2 gene the prevalence of parasites with deletions in Pfhrp 2 exon 2 was about a third of the false negative RDT results. The need to ensure rapid, accurate and reliable malaria diagnosis requires continuous surveillance of parasites with Pfhrp 2 gene deletions.